The Effectiveness Of Using Pictures of The Malayâ Folklores for Early Child Hood Reading Readiness - Kurnia, Rita; Hukmi, Hukmi; Satria, Defni (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study is originated from observations that showed reading readinesses of children are low in Siak Sri Inderapura. This condition must be solved to improve their reading readiness. Related to this, the researcher is interested in solving the problem by using pictures of Malayâ folklores. This is experimental research that uses quantitative methods with two-group: pre test and post-test. Based on the results of the t-test, it is obtained that t-score of -17,175 with a significance of 0,000. It can be concluded that there is a difference in reading readiness between experimental group and control group.